Autonomy or Control? Organizational Architecture and Corporate Attention to Stakeholders - Crilly, Donal; Sloan, Pamela (Organization Science, 2014)
Existing explanations of corporate attention to stakeholders overlook how organizations distribute the attention of their members. Combining interview and survey data at two levels of analysis, we show that executives’ assumptions about how best to configure their organizations have important implications for how their firms attend to stakeholders. We identify two types of organizational architecture: guided autonomy and cascaded control. The former enables specialized attention at the level of the individual manager and facilitates simultaneous attention to a large number of stakeholders; the latter restricts the autonomy of individual managers and leads to redundancy in attention. Our contribution is a framework that takes account of top manager frames and organizational architecture to articulate the relationship between individual- and organizational-level attention and to explain why some firms can address the concerns of multiple stakeholders simultaneously.